2016
DOI: 10.1155/2016/9093428
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hydrogen Bonding on Laminar Burning Velocity of Hydrous and Anhydrous Ethanol Fuel with Small Addition of n-Heptane

Abstract: The molecular structure of mixed hydrous and anhydrous ethanol with up to 10% v n-heptane had been studied. The burning velocity was examined in a cylindrical explosion combustion chamber. The result showed that the burning velocity of hydrous ethanol is higher than anhydrous ethanol and n-heptane at stoichiometric, rich, and very rich mixtures. The burning velocity of hydrous ethanol with n-heptane drops drastically compared to the burning velocity of anhydrous ethanol with n-heptane. It is caused by two reas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…Fig. 6, b shows that the laminar burning velocity of E90 decreases by the addition of water, this is in accordance with the previous research [14].…”
Section: Results Of the Combustion Characteristics Of The Ethanol And Lpg Mixturesupporting
confidence: 91%
See 3 more Smart Citations
“…Fig. 6, b shows that the laminar burning velocity of E90 decreases by the addition of water, this is in accordance with the previous research [14].…”
Section: Results Of the Combustion Characteristics Of The Ethanol And Lpg Mixturesupporting
confidence: 91%
“…3, b-d. This is in accordance with the previous research [14]. Abrupt flame speed reduction occurs from 5 % water content (W 5) to 7.5 % (W7,5) for E100 and E80, while for E90, the flame speed decreases gradually with the increase of water content.…”
Section: Calculation Of Laminar Burning Velocitysupporting
confidence: 93%
See 2 more Smart Citations
“…Many factors affect the combustion process, among which are fatty acids, polarity and the potential of electricity from fatty acids. Gas-fired research has also been examined by [8,9], revealing speed in the combustion chamber. The results showed that the hydro ethanol combustion rate was higher than anhydrous ethanol and N-Heptane in the stoichiometric mixture.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%